2013
DOI: 10.1002/bjs.9260
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of randomized clinical trials on safety and efficacy of biliary drainage before surgery for obstructive jaundice

Abstract: PBD in patients undergoing surgery for obstructive jaundice is associated with similar mortality but increased serious morbidity compared with no PBD. Therefore, PBD should not be used routinely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 39 publications
0
57
1
3
Order By: Relevance
“…[5][6][7][8] However, in Japan, preoperative biliary drainage is generally carried out. This is attributed to the fact that appropriately conducted preoperative biliary drainage can decrease the risk of postoperative complications 22 and that surgical waiting time, including detailed preoperative examinations, is usually several weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] However, in Japan, preoperative biliary drainage is generally carried out. This is attributed to the fact that appropriately conducted preoperative biliary drainage can decrease the risk of postoperative complications 22 and that surgical waiting time, including detailed preoperative examinations, is usually several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] The development of preoperative cholangitis after preoperative drainage has been reported to increase the incidence of postoperative complications, particularly pancreatic fistula. 9 Pancreatic fistula is a risk factor for surgical site infection.…”
mentioning
confidence: 99%
“…In a recent meta-analysis Y. Fang et al [25] found no strong evidence to support "routine preoperative biliary drainage." Large clinical trials are needed to determine the threshold level of bilirubin that will indicate which patients should undergo biliary drainage before surgery.…”
Section: What Are the Indications For Plastic Versus Metal Stent In Mmentioning
confidence: 98%
“…[40][41][42][43][44][45] Major drawbacks of these meta-analyses are the inclusion of retrospective series, methodological flaws, and the inclusion of patients who underwent percutaneous PBD or endoscopic PBD. Table 2 shows the results of the most recent metaanalyses.…”
Section: Preoperative Biliary Drainage Versus Early Surgerymentioning
confidence: 99%